2005
DOI: 10.1093/ps/84.7.1022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bt corn on broiler growth performance and fate of feed-derived DNA in the digestive tract

Abstract: The aim of the study was to evaluate the effect on broiler performance of transgenic Bacillus thuringiensis (Bt) corn containing the Cry1A(b) protein compared with the corresponding near isogenic corn and to analyze the degradation of the Cry1A(b) gene in the digestive tract. Ross male broilers (432) were fed for 42 consecutive days with diets containing Bt or isogenic corn. Diet, Bt corn, and the isogenic form of the Bt corn were analyzed for composition and aflatoxin B1, fumonisin B1, and deoxynivalenol cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
8
29
0
Order By: Relevance
“…Duggan et al reported that only a short cry gene (211-bp) was detected in rumen fluid when sheep were fed Bt corn 19 . Rossi et al detected a cry gene (1800-bp) only in gizzard contents, and there were no significant differences in the detection frequency of the other corn genes between Bt and isogenic corn fed to broilers 40 . They concluded that DNA derived from transgenic feed undergoes the same fate as isogenic feed.…”
Section: Fate Of Transgenic Plant Dna and Proteinmentioning
confidence: 98%
“…Duggan et al reported that only a short cry gene (211-bp) was detected in rumen fluid when sheep were fed Bt corn 19 . Rossi et al detected a cry gene (1800-bp) only in gizzard contents, and there were no significant differences in the detection frequency of the other corn genes between Bt and isogenic corn fed to broilers 40 . They concluded that DNA derived from transgenic feed undergoes the same fate as isogenic feed.…”
Section: Fate Of Transgenic Plant Dna and Proteinmentioning
confidence: 98%
“…In addition, in both USA and Argentina, corn was grown in less favourable weather conditions for fungal development compared with that planted in the humid tropical condition of Indonesia. Furthermore, the use of genetically engineering Bt corn resistant to insect attack in most US farms significantly decreased mycotoxin contamination (Chen et al 2004;Rossi et al 2005) because insect attack caused open wounds on kernels which facilitated fungus infection (Hawk 2004). …”
Section: Effect Of Harvest Seasons On Mycotoxin Levelmentioning
confidence: 99%
“…In the case of vertebrates, the fate of DNA from GM corn and soybean has been extensively monitored in cattle, sheep, pigs and poultry (Aeschbacher et al, 2005;Beagle et al, 2006;Chowdhury et al, 2004;Deaville and Maddison, 2005;Duggan et al, 2003;Einspanier et al, 2001;Jennings et al, 2003aJennings et al, , 2003bMazza et al, 2005;Nemeth et al, 2004;Sharma et al, 2006;Tony et al, 2003). DNA segments can survive intestinal juices and multicopy forms of DNA could be detected in some tissues examined in chickens (muscle, liver, spleen or kidney), but not in eggs (Einspanier et al, 2001).…”
Section: Hgt From Gm Plants To Animalsmentioning
confidence: 99%
“…One report of transgenic DNA in organs of pigs could not demonstrate the presence of an intact gene or integration into the genome of somatic cells (Sharma et al, 2006). In all cases, there was extensive degradation of DNA in the gastrointestinal tract, reducing the size and frequency of DNA transfers (Beagle et al, 2006;Chambers et al, 2002;Chowdhury et al, 2003;Deaville and Maddison, 2005;Phipps et al, 2003;Rossi et al, 2005;Wiedemann et al, 2006). Therefore, the GM feeding studies show the potential for transient gene transfer to animal somatic cells but not germ line cells (van den Eede et al, 2004).…”
Section: Hgt From Gm Plants To Animalsmentioning
confidence: 99%